Chariot of life : liberation war, politics and sojourn in jail - Chowdhury, Tawfiq-e-Elahi (Dhaka, Bangladesh : Shrabon Prokashani, 2018)
Memoirs of an adviser to the Prime Minister of Bangladesh.
AAL
Development Book Agency, Donated by Akbar Ali Khan (38296, 38541)
Keywords: Chowdhury, Tawfiq-e-Elahi.; Bangladesh -- History -- Revolution, 1971 -- Personal narratives; Bangladesh -- Officials and employees -- Personal narratives